Synchronous toughening and strengthening of the immiscible polylactic acid/thermoplastic polyurethane (PLLA/TPU) blends via the interfacial compatibilization with Janus nanosheets. (18th August 2022) - Guan, Jipeng; Luo, Wentao; Lu, Shifang; Yang, Yaru; Shen, Xiaojun; Tang, Bolin; Li, Yongjin
Abstract: In the polymer blends, strength is usually compromised to toughness after feeding the specialty additives and/or toughening agents. Herein, the functional Janus nanosheets (JNSs) with grafting PU chains and epoxide groups on the opposite sides of the silica nanosheets have been synthesized successfully, denoted as PU-SiO2 -epoxy JNSs. The functional JNSs as the compatibilizers are incorporated into the typical toughened polylactic acid/thermoplastic polyurethane (PLLA/TPU) blend. In the melt blending process, PLLA chains were in situ grafted onto the side of JNSs with the reaction between epoxide groups on the JNSs and the carboxyl acid groups of the PLLA. Notably, the obtained PU-SiO2 -PLLA JNSs preferred to assembled at the interface owing to the amphiphilicity and Pickering effect. The interfacial adhesion was greatly enhanced via the selective chain entanglement between grafted chains on the JNSs and blending parts. At 1.0 wt % JNSs loading, the elongation at break increased from 31.4 ± 2.3% to 362.6 ± 19.7% and the modulus increased from 1.0 ± 0.02 GPa to 1.9 ± 0.03 GPa. The JNSs jammed at the interface can act as the stiff shell outside the TPU island which is beneficial for transferring stress under external force. The impact strength reached nearly 100% enhancement after feeding 1.0 wt% JNS. This report provides a new possibility to realize synchronously toughening and strengthening of the polymer blends with the functional Janus nanosheets. Graphical abstract: Image 1